2018
DOI: 10.30659/ijibe.3.1.401-409
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Zakat in Business Development of Smes (Study on Baznas Semarang, Central Java, Indonesia)

Abstract: Poverty in developing countries including Indonesia still an unresolved phenomenon. The distribution of assistance through productive zakat is believed to be one of the solutions in alleviating poverty by giving zakat which used for working capital of small and medium-sized businesses. This study examined the role of productive zakat given to SMEs in the city of Semarang through the Badan Amil Zakat Nasional (BAZNAS) Semarang. The result showed that productive zakat had significant positive effect on business … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
3
0
1
Order By: Relevance
“…Proper management of Zakat can lead to sustainable economic prosperity for the community. 10 This research is similar to Mohammad Nizarul Alim's study, which found that productive Zakat management can help alleviate poverty and improve the economic well-being of society. Productive Zakat has more benefits than just consumption.…”
Section: Introductionsupporting
confidence: 83%
“…Proper management of Zakat can lead to sustainable economic prosperity for the community. 10 This research is similar to Mohammad Nizarul Alim's study, which found that productive Zakat management can help alleviate poverty and improve the economic well-being of society. Productive Zakat has more benefits than just consumption.…”
Section: Introductionsupporting
confidence: 83%
“…Many BAZ and LAZ have allocated such funds for productive economic empowerment, including assistance to MSEs; however, only a few of them have openly reported how much money was distributed for each mustahik or SME. Sukesti and Budiman (2018), for instance, investigated and recorded that the amount of zakat received for working capital was between IDR500,000 and IDR2,500,000. Using this reference, the upper limit is equal to ten times the micro-KUR loan limit.…”
Section: Could Zis Funds Be Used As Collateral?mentioning
confidence: 99%
“…Zakat produktif adalah penyediaan, pengelolaan, dan penyaluran dana zakat yang bersifat produktif, yang memberikan manfaat dan efek jangka panjang bagi penerima zakat. 12 Jumlah dana zakat produktif diberikan kepada mustahik dijadikan sebagai modal usaha. Faktor modal memiliki peranan yang sangat penting dalam kegiatan produktif dan pengembangan usaha, sesuai dengan teori bahwa modal akan membantu faktor produksi lain untuk lebih produktif, sehingga seharusnya bantuan modal akan meningkatkan kesejahteraan penerimanya.…”
Section: A Pendahuluanunclassified